Effect of a Cationic Surfactant on Microemulsion Globules and Drug Release from Hydrogel Contact Lenses - Cesar Torres-Luna; Naiping Hu; Abdollah Koolivand; Xin Fan; Yuli Zhu; Roman Domszy; Jeff Yang; Arthur Yang; Nam Sun Wang (MDPI AG, 2019)
The present study evaluates the in vitro release of diclofenac sodium (DFNa) from contact lenses based on poly-2-hydroxyethyl methacrylate (pHEMA) hydrogels containing an embedded microemulsion to extend release duration. The oil (ethyl butyrate)-in-water microemulsion systems are prepared with two non-ionic surfactants, Brij 97 or Tween 80, together with a long-alkyl chain cationic surfactant, cetalkonium chloride (CKC). Without CKC, Brij 97 or Tween 80-based microemulsions showed average droplet sizes of 12 nm and 18 nm, respectively. The addition of CKC decreased the average droplet sizes to 2−5 nm for both non-ionic surfactants. Such significant reduction in the average droplet size corresponds to an increase in the DFNa release duration as revealed by the in vitro experiments. Contact lens characterization showed that important properties such as optical transparency and water content of Brij 97-based contact lenses with cationic microemulsions was excellent. However, the optical transparency of the corresponding Tween 80 based contact lenses was unsatisfactory. The results indicate that cationic microemulsion-laden contact lenses can benefit from combinatory effects of microemulsions and cationic surfactant at low CKC weight percentage, e.g., with the release of 70% of the drug in 45, 10, and 7 h for B97-CKC-0.45%, CKC-0.45%, and control lenses, respectively. However, the microemulsion effect on extending DFNa release became negligible at the highest CKC weight percentage (1.8%).